DIFFERENCES IN THE MUSCLE ONSET TIMING BETWEEN LANDING POSTURES DECIDED BEFORE AND DURING JUMP-LANDING. Issue 7 (11th March 2014) - Sasaki, R; Yukio, U; Eri, F
Abstract : Backgraound: Jump-landing is a well-studied movement that causes sports injuries. Objective: The purpose of this study was to clarify the differences in the onset timing of the muscles during jump-landing among landing postures decided before and during landing. Design: Experimental study. Setting: Youth sports. Participants: 8 healthy female college students volunteered. Interventions: Jump-landing was performed from a 40 cm height box with both legs or a single leg. The landing posture was decided before or during landing. The onset timing of the vastus medialis (VM), vastus lateralis (VL), semmembranosus (SM) and biceps femoris (BF) was determined using the electromyography (EMG). The onset timing of muscle was identified as the first point that exceeded the mean baseline +3SD of the EMG amplitude. The baseline was set as the EMG amplitude at 100 ms after toe-off from the box. The landing duration was normalized in 100%. Main outcome measurements: A deley of the onset timing of muscles may be risk factor of injury during jump-landing when the landing posture is decided late. Results: The onset timing for both legs where the posture was decided before landing was 83.8±15.5%, 82.2±13.4%, 76.8±10.1%, 77.6±6.6% for the VM, VL, SM, BF, respectively; no significant defferences were noted among the muscles. During single-leg landing, values were 74.3±19.1%, 73.4±15.6%, 71.2±11.9%, 72.4±6.9%, respectively; the values significantly deffered for the VM and VL between movements with both legs and single leg (P<.05). No significant differences between cases where the landing posture was decided before and during landing. Conclusions: The onset timing of muscles did not significantly differ according to the time at which the landing posture was decided. However, muscle activities were only assessed during successful trials, and a significant difference may be noted if failed trials are included.